Oxidative physiology is weakly associated with pigmentation in birds. Issue 8 (11th August 2022) - Marton, Attila; Vágási, Csongor I.; Vincze, Orsolya; Bókony, Veronika; Pap, Péter L.; Pătraș, Laura; Pénzes, Janka; Bărbos, Lőrinc; Fülöp, Attila; Osváth, Gergely; Ducatez, Simon; Giraudeau, Mathieu
Abstract: The mechanistic link between avian oxidative physiology and plumage coloration has attracted considerable attention in past decades. Hence, multiple proximal hypotheses were proposed to explain how oxidative state might covary with the production of melanin and carotenoid pigments. Some hypotheses underscore that these pigments (or their precursors, e.g., glutathione) have antioxidant capacities or function as molecules storing the toxic excess of intracellular compounds, while others highlight that these pigments can act as pro‐oxidants under specific conditions. Most studies addressing these associations are at the intraspecific level, while phylogenetic comparative studies are still scarce, though needed to assess the generality of these associations. Here, we tested whether plumage and bare part coloration were related to oxidative physiology at an interspecific level by measuring five oxidative physiology markers (three nonenzymatic antioxidants and two markers of lipid peroxidative damage) in 1387 individuals of 104 European bird species sampled during the breeding season, and by scoring plumage eumelanin, pheomelanin, and carotenoid content for each sex and species. Only the plasma level of reactive oxygen metabolites was related to melanin coloration, being positively associated with eumelanin score and negatively with pheomelanin score. Thus, our results do not support the role of antioxidant glutathione in driving variation in melanin synthesis across species. Furthermore, the carotenoid scores of feathers and bare parts were unrelated to the measured oxidative physiology parameters, further suggesting that the marked differences in pigmentation across birds does not influence their oxidative state. Abstract : Both oxidative physiology and plumage coloration are important foci of avian research in the past decade, and intraspecific studies suggest multiple mechanistic links between the antioxidant system and pigmentation. We performed a large‐scale comparative analysis on 104 European bird species, and found that species‐specific oxidative physiology and plumage coloration evolved largely independently of each other. Out of five oxidative physiological markers measured only the plasma level of reactive oxygen metabolites was related to melanin coloration, being positively associated with eumelanin score, and negatively with pheomelanin score. Thus, our results do not support the role of antioxidant glutathione in driving variation in melanin synthesis across species. Furthermore, the carotenoid scores of feathers and bare parts were unrelated to the measured oxidative physiology parameters, further suggesting that the marked differences in pigmentation across birds does not influence their oxidative state.